Peranan Kelapa Sawit Dalam Perekonomian Daerah Provinsi Jambi: Analisis Input-Output Tahun 2010 - Edwin Mahatir Muhammad Ramadhan; Hermanto Siregar; Bambang Juanda (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Abstract: This study aims to analyze the economy of Jambi in 2010, it analyzes the link and multiplier effect sectors, and the contribution of oil palm to regional economic of Jambi province. The results showed that during the period of 2000 and 2010, the economy of Jambi overall has developed very significantly as its output reach Rp18.087.666 million in 2000 to Rp103.362.415 trillion in 2010. Some of structural parameters of the I-O analysis also have increased. Backward direct effect reach 0,3423 for palm oil and 0,3792 for CPO industry in 2010. Forward direct effect reach 0,0077 for palm oil and 0,0090 for CPO industry in 2010. Output multiplier of type I 1,4301 for palm oil and 1,5516 for CPO industry in 2010. Income multiplier of type I 1,2465 for palm oil and 2,8678 for CPO industry in 2010. Em-ployment multiplier of type I 1,2584 for palm oil and 3,6977 for CPO industry in 2010.Keywords: local economy, oil palm, Jambi province, input-output analysis, multiplier effect